Warming-induced northwestward migration of the East Asian monsoon rain belt from the Last Glacial Maximum to the mid-Holocene - Yang, Shiling (Proc Natl Acad Sci U S A, 2015)
Glacial–interglacial changes in the distribution of C(3)/C(4) vegetation on the Chinese Loess Plateau have been related to East Asian summer monsoon intensity and position, and could provide insights into future changes caused by global warming. Here, we present δ(13)C records of bulk organic matter since the Last Glacial Maximum (LGM) from 21 loess sections across the Loess Plateau. The δ(13)C values (range: –25‰ to –16‰) increased gradually both from the LGM to the mid-Holocene in each section and from northwest to southeast in each time interval. During the LGM, C(4) biomass increased from <5% in the northwest to 10–20% in the southeast, while during the mid-Holocene C(4) vegetation increased throughout the Plateau, with estimated biomass increasing from 10% to 20% in the northwest to >40% in the southeast. The spatial pattern of C(4) biomass in both the LGM and the mid-Holocene closely resembles that of modern warm-season precipitation, and thus can serve as a robust analog for the contemporary East Asian summer monsoon rain belt. Using the 10–20% isolines for C(4) biomass in the cold LGM as a reference, we derived a minimum 300-km northwestward migration of the monsoon rain belt for the warm Holocene. Our results strongly support the prediction that Earth's thermal equator will move northward in a warmer world. The southward displacement of the monsoon rain belt and the drying trend observed during the last few decades in northern China will soon reverse as global warming continues.